Multivariable control algorithm for laboratory experiments in wind energy conversion. (November 2015) - Merabet, A.; Islam, Md.A.; Beguenane, R.; Trzynadlowski, A.M.
Abstract: Advanced experimentation with wind energy conversion systems is described. The real time multivariable control of a wind turbine is designed for investigation of theoretical concepts and their physical implementation. The control system includes a speed controller and a disturbance estimator for enhanced robustness of the control system. In order to provide students with deeper understanding of wind energy and energy extraction, a maximum power point tracking algorithm is developed and integrated into the control system. The multivariable control system is implemented in a small wind turbine laboratory system. A power electronic interface is based on two DC–DC converters: a buck converter for control of the speed and a boost converter controlling the load voltage. Experimental results demonstrate effectiveness of the multivariable control system for a wind turbine providing maximum power extraction. The experiment can be reconfigured for teaching various control concepts to both undergraduate and graduate students. Highlights: Advanced experimentation with laboratory scale wind energy conversion system is described. The multivariable control of a wind turbine allows the investigation of theoretical concepts and physical implementation. The control system includes a speed controller and a disturbance estimator for enhanced robustness of the control system. A maximum power point tracking algorithm is developed and integrated into the control system. Experimentation demonstrates effectiveness of the multivariable control system for maximum power extraction wind turbine.